PENTINGNYA PERANAN SKILL DAN MENU KNOWLEDGE WAITER/WAITERS TERHADAP KEPUASAN PELANGGAN DI FOOD AND BEVERAGE SERVICE DEPARTEMENT - Fitria Earlike AS; Tutut Mega Mukti Atalina (Jurnal Pariwisata Pesona, 2016)
The Background of this research from the topic is the lack of waiter/ waitresss skills and menu knowledge when doing the food and beverage services. The purpose of this research is to know the importance of waiter /waitresss skills and menu knowledge toward guest satisfaction. Method of the research was descriptive qualitative which was collected data by using interview, observation, documentation, quitionare and study of literature. The rusult shows that guests satisfaction are decreased and proved by the respondents quitionare result which shows that the guests are not satified with the waiter/ waitress skills and menu knowledge.